ANALISIS PENGARUH LITERASI KEUANGAN, KONFORMITAS, DAN STATUS SOSIAL EKONOMI ORANG TUA TERHADAP PERILAKU KONSUMTIF GENERASI Z DI KOTA MALANG - Nurman Setiawan Fadjar; Girsang, Cyntia Agustina (Journal of Development Economic and Social Studies, 2022)
This study aims to determine the effect of financial literacy, conformity, and parental socio-economic status on the consumption behavior of the generation Z in Malang city. This research is descriptive quantitative research with data collection methods through questionnaires distributed to individuals categorized as Generation Z in Malang City with a sample size of 100 people. The collected data were processed and tested using the Spearman Rank correlation method to determine the effect partially, and the Kendall W Concordance to determine the effect simultaneously. The results showed that the financial literacy (X1) partially have a negative and significant effect on consumption behavior (Y), conformity (X2); and parental socio-economic status (X3) partially have a positive and significant effect on consumption behavior (Y). From the results of simultaneous statistical testing, it was found that the financial literacy (X1), conformity (X2), and parental socio-economic status (X3) simultaneously have a significant effect on consumption behavior (Y). Based on the mean rank of the concordance of Kendall w, it was also found that parental socio-economic status is the variable that has the most effect on the consumptive behavior of Generation Z in Malang City.